2014
DOI: 10.1007/s10014-014-0195-z
|View full text |Cite
|
Sign up to set email alerts
|

Rosette-forming glioneuronal tumour (RGNT) of the fourth ventricle: a highly aggressive case

Abstract: Experience of RGNT is limited. The prognostic significance of the histological findings of vascular proliferation and necrosis is still unknown. The clinical improvement in our patient endorses our decision to perform aggressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The SLC44A1‐PRKCA fusion, which is frequently observed in PGNTs, was not detected in the two RGNTs tested in the previous work . The hallmarks of diffuse glioma, namely IDH1/2 mutation and 1p/19q codeletion, were absent in all tested cases, according to previous reports, as well as in the present study .…”
Section: Discussionsupporting
confidence: 82%
“…The SLC44A1‐PRKCA fusion, which is frequently observed in PGNTs, was not detected in the two RGNTs tested in the previous work . The hallmarks of diffuse glioma, namely IDH1/2 mutation and 1p/19q codeletion, were absent in all tested cases, according to previous reports, as well as in the present study .…”
Section: Discussionsupporting
confidence: 82%
“…This study describes for the first time a comprehensive genetic characterization of a case of RGNT of the fourth ventricle arising in the spinal cord. This is not the usual presentation, yet it has been previously reported [ 17 , 18 ]. The MRI images showed a relatively well-demarcated lesion, with low and high intensities in T1 and T2, respectively, which corroborate findings of other studies [ 8 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 67%
“…After systematic review and statistical analyses, we found that pediatric age, purely solid nature of the tumor, and inadequate resection may be risk factors associated with progression events. The efficacies of adjuvant radiotherapy and chemotherapy are yet to be determined for RGNTs owing to limited administration experience [ 3 , 12 , 13 , 16 , 44 ], and their confirmative role requires further assessment. Although progressive events are rare for RGNTs, clinicians should be aware of these potential events and a long-term close follow-up is needed.…”
Section: Discussionmentioning
confidence: 99%